Real-world experience of lenvatinib in patients with advanced anaplastic thyroid cancer - Kim, Mijin; Ahn, Jonghwa; Song, Dong Eun; Yoon, Jee Hee; Kang, Ho-Cheol; Lim, Dong Jun; Kim, Won Gu; Kim, Tae Yong; Kim, Won Bae; Shong, Young Kee; Jeon, Min Ji; Kim, Bo Hyun (Endocrine, 2021)
Purpose We aimed to evaluate the clinical efficacy and safety of lenvatinib in patients with advanced anaplastic thyroid cancer (ATC) in real-world practice. Methods This multicenter, retrospective cohort study included 14 patients with advanced ATC who received lenvatinib. We evaluated the response rate according to RECIST. Results Ten patients had de novo ATC, and lenvatinib was used as a neoadjuvant treatment in eight patients. During a median follow-up of 6.7 months, patients received lenvatinib at a median dose of 13 mg daily. Overall, four patients (29%) showed partial response, nine (64%) had stable disease, and one (7%) had progressive disease. Tumor burden was reduced in 13 patients (93%), and the median best percent change from the baseline was −15.8%. The median progression-free survival and overall survival were 5.7 months (95% confidence interval [CI], 2.2–8.3) and 6.7 months (95% CI, 3.0–8.4), respectively. All patients experienced adverse events (AEs). Most AEs were manageable but two AEs—tracheal perforation, and pneumothorax and pneumomediastinum—were life-threatening. One patient underwent flap surgery for reconstruction of their tracheal perforation, and another died of pneumothorax and pneumomediastinum, which seemed to be related to lenvatinib. Conclusions In this multicenter real-world study, lenvatinib demonstrated limited clinical activity in advanced ATC. It effectively reduced the tumor burden but showed doubtful survival benefit. Although most AEs were manageable, one fatal AE was related to rapid tumor shrinkage. Further studies are needed to clarify the efficacy and optimal dose of lenvatinib in patients with advanced ATC.